Impacts of conversion of tropical peat swamp forest to oil palm plantation on peat organic chemistry, physical properties and carbon stocks - Tonks, Amanda J.; Aplin, Paul; Beriro, Darren J.; Cooper, Hannah; Evers, Stephanie; Vane, Christopher H.; Sjögersten, Sofie (Elsevier, 2017)
Ecosystem services provided by tropical peat swamp forests, such as carbon (C) storage and water regulation, are under threat due to encroachment and replacement of these natural forests by drainage-based agriculture, commonly oil palm plantation. This study aims to quantify how the chemical and physical properties of peat change during land conversion to oil palm. This will be addressed by comparing four separate stages of conversion; namely, secondary peat swamp forests, recently deeply drained secondary forests, cleared and recently planted oil palm, and mature oil palm plantation in North Selangor, Malaysia. Results indicate accelerated peat decomposition in surface peats of mature oil palm plantations due to the lowered water table and altered litter inputs associated with this land-use change. Surface organic matter content and peat C stocks at secondary forest sites were higher than at mature oil palm sites (e.g. C stocks were 975 ± 151 and 497 ± 157 Mg ha− 1 at secondary forest and mature oil palm sites, respectively). Land conversion altered peat physical properties such as shear strength, bulk density and porosity, with mirrored changes above and below the water table. Our findings suggest close links between the organic matter and C content and peat physical properties through the entire depth of the peat profile. We have demonstrated that conversion from secondary peat swamp forest to mature oil palm plantation may seriously compromise C storage and, through its impact on peat physical properties, the water holding capacity in these peatlands.